Cardiometabolic healthy and unhealthy obesity: does vitamin D play a role?. Issue 8 (November 2017) - Piantanida, Eliana; Gallo, Daniela; Veronesi, Giovanni; Dozio, Eugenia; Trotti, Eugenia; Lai, Adriana; Ippolito, Silvia; Sabatino, Jessica; Tanda, Maria Laura; Toniolo, Antonio; Ferrario, Marco; Bartalena, Luigi
Abstract : Objective: The aim of this observational study was to clarify the link between vitamin D status and metabolic syndrome (MetS) in people with visceral obesity. Design and methods: One hundred ninety-six consecutive patients (152 women; mean age 51 ± 13 years) with visceral obesity (mean body weight 103 ± 20 kg, mean waist circumference (WC) 119 ± 13 cm) were enrolled at the Obesity Outpatient Clinic of the University of Insubria in Varese. Anthropometric measurements were recorded. Laboratory tests, including vitamin D (25(OH)D)), fasting blood glucose (FBG), lipid profile, liver and kidney function tests were assessed. Vitamin D status was defined according to the European Society of Endocrinology guidelines, MetS to the 2009 harmonized definition. Results: An inverse association emerged among 25(OH)D, body mass index (BMI) ( P = 0.001) and WC (all P = 0.003). Serum 25(OH)D levels were inversely related to FBG and systolic blood pressure (SBP) (respectively, P = 0.01 and 0.02). Median serum 25(OH)D levels were 13.3 ng/mL (CI 95% 12; 15) in MetS and 16 ng/mL (CI 95% 14; 18) ( P = 0.01) in non-MetS patients. Among patients with MetS, lower 25(OH)D concentrations were related to higher risk of hypertension (HT) (odds ratio (OR) 1.7, CI 95%, 0.7;4) and hyperglycemia (IFG)/type 2 diabetes (OR 5.5, CI 95% 2; 14). Conclusion: Vitamin D status and MetS are inversely correlated in visceral obesity, particularly with regard to glucose homeostasis and BP. More extensive studies are required to investigate the potential for causality.